(untitled) (Al-Aasar, 2025)
This critical project is an analytical project that provides a comparative analysis of the concept of Qawam (قَوّام) as deemed by Dr. Muhammad Asad and how it is reflected by classical Islamic scholars. The verse of Quran (The 4:34) brings the word Qawamun and it is traditionally regarded by the classical exegetes like Al-Tabari, Ibn Kathir and Al-Qurtubi as an indicator of male dominance, leadership and responsibility in the home. The socio-economic responsibility of men is used in elucidating their superiority over women in family affairs by their modernist Quranic translator and thinker, Dr. Muhammad Asad. He points out that the term does not mean that males are inherently dominant but it is a functional duty that is informed by the current economic and societal set-ups. This paper compares and contrasts these two interpretations through tafsir literature, linguistic and socio-historic considerations, as they are broadly reflected in the rest of the Quran concerning justice and compassion. The paper concludes that the perspective of Dr. Asad is more compatible with the current era of gender equality and individual accountability whilst classical scholars were operating in a patriarchal society where their interpretation of Qawam may still hold a lot of relevance. This reading is not a denial of tradition but rather a re-involvement of tradition by using the ethical reason and awareness of the surrounding. Therefore, it is a way to reconcile the conventional scholarship and contemporary human rights discourse, and it is a comprehensive and loyal way to Islamic gender ethics.